Meningkatkan Kesediaan Membayar Konsumen melalui CRM dan Kualitas Pelayanan: Peran Kunci Kepuasan Konsumen sebagai Mediator - Santoso, Bagastya Christian; Santoso, Nelvina Christanti; Santoso, R Tri Priyono Budi (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study aims to explain how customer satisfaction influences customer satisfaction and how customer relationship management, service quality, and customer satisfaction affect consumer willingness to pay. It also explains how customer satisfaction acts as a mediator between customer satisfaction and the relationship between customer relationship management and service quality and consumer willingness to pay. 126 respondents were chosen for the study using a purposive sampling technique, and the study was carried out at the Puri Saron Hotel Denpasar using a questionnaire. Path analysis and the Sobel Test were used to examine the study's findings and assess the mediation hypothesis. The study's findings provide an explanation for the substantial positive correlation that exists between the dependent and independent variables. In addition, the relationship between customer relationship management and service quality and willingness to pay of the customer can be mediated by the variable of customer satisfaction.